Time is muscle : a systematic review investigating the role of remote ischaemic preconditioning and glucose-insulin-potassium infusions as adjunctive therapies to revascularisation in coronary artery disease - Mothilal, Shikar (Division of Cardiology, 2015)
In the management of coronary artery disease (CAD) most advances have concerned improvements in catheter-based interventional techniques and complex pharmacotherapy, with an emphasis on time, which unfortunately, cannot always achieved. However, simple measures with reassuring benefit that can be performed even by non-cardiologists have been largely overlooked, or understated. These include limiting reperfusion injury by remote ischaemic conditioning (RIPC), a powerful protective mechanism that can be elicited by the transient occlusion of blood flow to a limb with a blood pressure cuff. More controversially, glucose-insulin-potassium (GIK) therapy in early ST elevation myocardial infarction (STEMI) has the potential to improve outcomes especially when timely restoration of vessel patency is difficult to achieve. This systematic review will evaluate the role of these therapies as adjuncts to revascularisation for treating coronary artery disease either electively or during an acute coronary syndrome. Objectives: To determine if RIPC or GIK therapy for CAD leads to reduced mortality (primary objective), infarct size, cardiac enzyme release or major adverse cardiac and cerebral events (MACCE) and to identify adverse effects associated with RIPC or GIK (secondary objectives).